Landscape design principles - Clokey, Jora.; Stoltz, Ronald R.; San Luis Video Publishing (Los Osos, CA San Luis Video Pub., 2004)
Learn how to incorporate plants, topography and hardscape features with the basic artistic principles of form, line,texture and colour, and more. Learn how to design landscapes which are appropriate, novel and well built.
DVD
Keywords: Landscape architecture; Landscape design; Video discs